1998
DOI: 10.1021/js970271g
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Distribution and Intracellular Dynamics of a Spin-Labeled Analogue of Doxorubicin by Fluorescence and EPR Spectroscopy

Abstract: Fluorescence spectroscopy revealed a dramatic difference between the intracellular distributions of doxorubicin (DOX) and its paramagnetic analogue, ruboxyl (Rb). Modification of the anthracyclin structure by introduction of a paramagnetic label at position 14 in the DOX molecule resulted in reduced DNA binding and enhanced partitioning into phospholipid membranes, as evidenced by the fluorescence-quenching experiments. Higher partitioning into cell membranes resulted in stronger intracellular fluorescence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 4 publications
4
31
0
Order By: Relevance
“…This is consistent with our previous results showing that more Dox and Ruboxyl accumulate in the cells during ultrasonic exposure [1,6,10,15]. We postulate that the shear events associated with ultrasound and accompanying cavitation events leads to stress on the cell membrane and/or the cell wall and renders the cell more permeable to the passive transport of the drugs or the fluorescent probes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with our previous results showing that more Dox and Ruboxyl accumulate in the cells during ultrasonic exposure [1,6,10,15]. We postulate that the shear events associated with ultrasound and accompanying cavitation events leads to stress on the cell membrane and/or the cell wall and renders the cell more permeable to the passive transport of the drugs or the fluorescent probes.…”
Section: Discussionsupporting
confidence: 93%
“…We have previously established the fact that ultrasound releases Dox and other drugs from micelles [2,5-10]. The following discussion pertains to if and how ultrasound also enhances uptake of the drug into the cells.…”
Section: Discussionmentioning
confidence: 99%
“…These micelles are large enough to escape renal excretion while being small enough to extravasate at the tumor site. Antineoplastic agents can be easily sequestered inside the core of these polymeric micelles by the simple act of mixing [154,171], this avoiding the complexities involved with covalently boding the drug to the polymeric carrier [172]. Several studies have reported the effect of Pluronic surfactants in overcoming multidrug resistance (MDR) [173][174][175].…”
Section: Micellesmentioning
confidence: 99%
“…[50,73–75] The insertion depth and membrane destabilization of non-internalized DOX conjugates are dependent on a number of factors involving the chemical structure of anthracyclines. [76,77] The chemical structure of side chains of HPMA copolymer/DOX conjugates, the density of Pgp, and the number of DOX per conjugate may also influence the ability of DOX to destabilize the membrane. [19,34] The decreased IC 50 dose of conjugate 9 [P-(GFLG-DOX-mAb)] versus conjugate 7 [P-(GG-DOX-mAb)] for A2780/AD cells could reflect differences in the oligopeptide side chains used to link DOX to the HPMA copolymer backbone, and result in variation in the ability to disrupt the membrane.…”
Section: Discussionmentioning
confidence: 99%